Effects of the Use of Staphylococcus carnosus in the Curing Process of Meat with a Reduced Amount of Sodium Nitrite on Colour, Residue Nitrite and Nitrate, Content of Nitrosyl Pigments, and Microbiological and the Sensory Quality of Cooked Meat Product - Piotr Szymański; Beata Łaszkiewicz; Urszula Siekierko; Danuta Kołożyn-Krajewska (Journal of Food Quality)
The aim of the work was to apply the bacteria Staphylococcus carnosus ATCC 51365 in the meat curing process with the use of a reduced amount of sodium nitrite and to evaluate the effects of bacteria on residual nitrites and nitrates, the content of nitrosyl pigments, colour, pH, oxidation-reduction potential, microbiological, and the sensory quality of a cooked meat product. Three meat batters in cans were prepared: (C) a control batter cured with NaNO2—100 mg/kg, (L) a batter cured with NaNO2—15 mg/kg, and (LS) a batter cured with NaNO2—15 mg/kg and S. carnosus (107 CFU/g). The cans were stored at a temperature of 4°C for 24 h (curing time) and cooked. The analysis was carried out after production and after 4 and 8 weeks of storage. The use of denitrifying bacteria in the curing process with a reduced amount of sodium nitrite increased the availability of nitrite in the meat, by reducing nitrates formed as a result of a dismutation reaction. The reaction contributed to the formation of nitrosyl pigments in a larger quantity than in the treatment in which the denitrifying bacteria were not used. The LS treatment was characterized by the greatest redness. The colour of the LS treatment was stable during storage. No negative effect of S. carnosus on the sensory quality of the meat product was found. The use of S. carnosus had no influence on the microbiological quality of meat product during storage.